THE C-SUITE'S NEW MVP: WHY HUMAN CAPITAL IS NOW THE KEY STRATEGIC ASSET - Arief Sumarsono; Ramon Zamora; Dhenny Asmarazisa (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This article examines the transformative role of data analytics in modern human resource management, known as Data-Driven HR. The background outlines the shift from traditional, intuition-based HR practices to a strategic, evidence-based approach This article examines the pivotal shift recognizing human capital as the primary strategic asset in the modern knowledge economy. The background establishes the transition from industrial-era models, where physical and financial capital were paramount, to a landscape where innovation, agility, and intellectual property drive competitive advantage. The objective is to argue for the C-suite's direct ownership of human capital strategy, moving it beyond the traditional HR domain. The methodology involves a synthesis of contemporary business literature, analysis of corporate reporting trends, and review of executive leadership frameworks. The results indicate that organizations treating talent strategy as a core CEO and CFO priority demonstrate superior resilience, innovation, and financial performance. The discussion contends that this requires new metrics integrating human capital into financial analysis and a fundamental re-evaluation of leadership agendas. In conclusion, human capital is the new source of sustainable value, demanding a reformed strategic lens where talent outcomes are inseparable from business outcomes.